Epidemiology of Bleeding in Critically Ill Children - Sequeira, Jake; Nellis, Marianne E.; Karam, Oliver (Frontiers in Pediatrics, 2021)
Objective: Bleeding can be a severe complication of critical illness, but its true epidemiologic impact on children has seldom been studied. Our objective is to describe the epidemiology of bleeding in critically ill children, using a validated clinical tool, as well as the hemostatic interventions and clinical outcomes associated with bleeding. Design: Prospective observational cohort study. Setting: Tertiary pediatric critical care unit Patients: All consecutive patients (1 month to 18 years of age) admitted to a tertiary pediatric critical care unit Measurements and Main Results: Bleeding events were categorized as minimal, moderate, severe, or fatal, according to the Bleeding Assessment Scale in Critically Ill Children. We collected demographics and severity at admission, as evaluated by the Pediatric Index of Mortality. We used regression models to compare the severity of bleeding with outcomes adjusting for age, surgery, and severity. Over 12 months, 902 critically ill patients were enrolled. The median age was 64 months (IQR 17;159), the median admission predicted risk of mortality was 0.5% (IQR 0.2;1.4), and 24% were post-surgical. Eighteen percent of patients experienced at least one bleeding event. The highest severity of bleeding was minimal for 7.9% of patients, moderate for 5.8%, severe for 3.8%, and fatal for 0.1%. Adjusting for age, severity at admission, medical diagnosis, type of surgery, and duration of surgery, bleeding severity was independently associated with fewer ventilator-free days (p<0.001) and fewer PICU-free days (p<0.001). Adjusting for the same variables, bleeding severity was independently associated with an increased risk of mortality (adjusted odds ratio for each bleeding category 2.4, 95%CI 1.5;3.7, p<0.001). Conclusion: Our data indicate bleeding occurs in nearly one-fifth of all critically ill children, and that higher severity of bleeding was independently associated with worse clinical outcome. Further multicenter studies are required to better understand the impact of bleeding in critically ill children.